Application of Naive Bayes in Assessing Student Satisfaction with Facilities and Services at SMK Dastamaco - Novianti, Deny (SAN Scientific, 2023)
Education is one of the important factors that are highly considered. Starting from the selection of quality schools and also the background of good teachers. However, sometimes in order to get good facilities, of course, it is also balanced with a lot of costs. Maybe only parents who can afford it will not be a problem, but not so with parents of students whose economic conditions are middle to lower. SMK Dastamaco continues to strive to provide the best service and quality for students, so that parents feel safe and comfortable having entrusted their children to go to school. Usually, it is rare for schools to evaluate students' satisfaction with the service and quality of the existing school. Therefore, the school also lacks information about which side needs to be improved so that the school can be even better later. Based on the above problems, it is necessary to hold a differentiating classification to find out how many students are satisfied with the service and quality of SMK Dastamaco. And to classify it can use the Naive Bayes method, where later several criteria are used to be able to find out whether students are satisfied or dissatisfied with the service and quality of the school. From the test results conducted with 191 data, and as many as 27 as test data. An accuracy pattern of 0.556 stated Satisfied, and 0.222 expressed dissatisfied and also dissatisfied. Pendidikan merupakan salah satu faktor penting yang sangat difikirkan. Mulai dari pemilihan sekolah yang berkualitas dan juga latar belakang pengajarnya yang baik. Namun, terkadang agar mendapatkan fasilitas yang bagus, tentu pula diimbangi dengan biaya yang tidak sedikit. Mungkin baru para orang tua murid yang mampu tidak akan menjadi masalah, tapi tidak begitu dengan orang tua murid yang kondisi perekonomiannya menengah ke bawah. SMK Dastamaco terus berupaya untuk memberikan pelayanan dan kualitas yang terbaik bagi para siswa, agar para orang tuanya merasa aman dan nyaman telah menitipkan anaknya untuk bersekolah. Biasanya jarang ada sekolah yang melakukan evaluasi terhadap kepuasan para siswa terhadap pelayanan dan kualitas sekolah yang ada. Maka dari itu, pihak sekolah juga kurang mendapatkan informasi tentang sisi manakah yang perlu diperbaiki agar sekolah bisa jadi lebih baik lagi nantinya. Berdasarkan masalah di atas perlu diadakannya klasifikasi pembeda untuk mengetahui seberapa banyak siswa yang sudah merasa puas terhadap pelayanan dan kualitas dari SMK Dastamaco. Dan untuk mengklasifikasikannya dapat menggunakan metode Naive Bayes, dimana nantinya digunakan beberapa kriteria untuk dapat mengetahui apakah siswa merasa puas atau tidak puas terhadap pelayanan dan kualitas sekolah. Dari hasil pengujian yang dilakukan dengan data sebanyak 191, dan sebanyak 27 sebagai data tes. Didapatkan pola akurasi sebesar 0, 556 yang menyatakan Puas, serta 0, 222 yang menyatakan kurang puas dan juga tidak puas.